Multiple Sclerosis and Seizures: Clinical, Diagnostic and Therapeutic Correlations - C. Wood; S. Owen; S. Ebden; B. Anand; M. Wardle; K Hamandi; K. L. Kreft; N. P. Robertson; E. C. Tallantyre (Brain and Behavior)
ABSTRACT Introduction Seizures occur more commonly in people with multiple sclerosis (pwMS) than in the general population. Existing studies correlating clinical, diagnostic and therapeutic outcomes for pwMS and seizures are lacking. We determine the prevalence of seizure(s) in people with MS/clinically isolated syndrome (CIS) and characterize a population‐based cohort of pwMS/CIS and seizure(s). Methods We used the South Wales MS registry to identify all people with MS/CIS and a lifetime history of seizure living within Cardiff and Vale. Retrospective clinical data were extracted from electronic records. Prevalent populations of (i) lifetime history of seizure(s) (ii) epilepsy diagnosis in pwMS/CIS were calculated on the January 1st, 2020 for the catchment area. MR brain images nearest to time of first seizure were reviewed and compared to a contemporary, matched cohort of pwMS without seizures. Results We identified 49 historical cases of co‐existent MS/CIS and seizure(s). On January 1st, 2020, we found that 2.4% (23/950, 95% CI 1.4%–3.4%) of the prevalent population of people with MS/CIS had experienced a seizure and 2.1% (20/950, 95% CI 1.2%–3.0%) had a diagnosis of epilepsy, which is higher than the general population (0.76%). Seizure(s) occurred before other symptoms of MS in 15/49 and after MS in 34/49. One patient (2%) experienced a seizure during MS relapse. First seizure occurred during treatment with fingolimod in three patients and with fampridine in one patient. Analysis of MR brain images suggests that pwMS and seizures have a higher number of T2 lesions and more marked brain atrophy. Conclusion This study suggests that approximately 2.4% of people with MS/CIS are expected to experience seizure(s). Seizures in MS are associated with higher overall brain disease burden.